Fourth annual report of the Commissioner for scheduled castes and Scheduled tribes 1954 - India. Office of the commissioner for scheduled Castes and scheduled Tribes (Office of the commissioner for scheduled Castes and scheduled Tribes, 1954)
This is the Fourth Annual Report submitted to the President under Article 338 of the Constitution. It relates to the year 1954. These Annual Reports are submitted to the President before the end of February every year so that these are printed and placed in the hands of the Members of Parliament for discussions during the Budget Sessions. the discussions on the Third Annual Report, pertaining to the year 1953, have not yet concluded in the Lok Sabha and it is, therefore, likely that discussions on that Report as well as on this Report may be held together, during the present Budget Session.
Government of India
Government of India
Keywords: Scheduled Castes and Scheduled Tribes; Welfare and Social Conditions